Habitat Preferences of PokeA (Batissa violacea var. celebensis von Martens, 1897) Basic on Substrat Characterisation in Pohara River Southeast Sulawesi - Bahtiar Bahtiar; Muh. Fajar Purnama (Jurnal Moluska Indonesia, 2020)
This research is motivated by the lack of information about the habitat preferences of pokea clams in Pohara River, Southeast Sulawesi. This study aims to determine the density, distribution pattern and habitat preferences of pokea clams in the Pohara River, Southeast Sulawesi. This research was conducted for 6 months (April-September 2011). Sampling of pokea, water quality, and sediment texture was carried out in the Pohara River and analyzed at the FPIK UHO Laboratory. The density and distribution of pokea were calculated using a standard formula and analyzed using Mann Whitney and Chi Square respectively, while the habitat preferences based on different substrate textures were analyzed using Principal Component Analysis (PCA) and Cluster Analysis (CA) in the Multivariate Statistical Package (MVSP). The results showed that the density of pokea clams ranged from 117±96.78-816±594.84 ind/m2 which was distributed in cluster over the entire cross-section of the river. Pokea clams were found in all substrate textures from gravel to clay. The habitat preference of pokea clams indicated by the highest density was found in the clay texture. Pokea clams relatively do not like the habitat of coarse sand and gravel texture which is characterized by pokea population with the lowest density